2016
DOI: 10.1007/s00405-016-4127-x
|View full text |Cite
|
Sign up to set email alerts
|

Whole-brain changes in white matter microstructure after radiotherapy for nasopharyngeal carcinoma: a diffusion tensor imaging study

Abstract: Radiation-induced local white matter (WM) damage has been observed by diffusion tensor imaging (DTI) within a priori-defined regions of interest following radiotherapy (RT) for nasopharyngeal carcinoma (NPC). In this study, we aimed to detect WM changes throughout the brain of NPC patients by DTI. Tract-based spatial statistics (TBSS) was used to analyze DTI data from 81 NPC patients. Fractional anisotropy (FA) and mean diffusivity (MD) were quantified across the whole brain in separate groups: pre-RT, and <6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 24 publications
4
33
2
Order By: Relevance
“…This result is partially consistent with several previous studies (Duan et al, 2016, Lv et al, 2014). Duan et al (2016) detected lower fractional anisotropy (FA) in the frontal and parietal WM in the post-RT-ED group than that of the pre-RT group. Lv et al (2014) found GM volume deficit in the parietal cortex in NPC patients after RT.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This result is partially consistent with several previous studies (Duan et al, 2016, Lv et al, 2014). Duan et al (2016) detected lower fractional anisotropy (FA) in the frontal and parietal WM in the post-RT-ED group than that of the pre-RT group. Lv et al (2014) found GM volume deficit in the parietal cortex in NPC patients after RT.…”
Section: Discussionsupporting
confidence: 94%
“…In the post-RT-ED group, we have not found significantly changed cortical thickness in the temporal region, but previous DTI studies (Duan et al, 2016, Xiong et al, 2013) have detected abnormal temporal region in the post-RT-ED group. For example, using DTI method, Duan et al (2016) found higher mean diffusivity in the bilateral temporal regions in the post-RT-ED group than that of the pre-RT group.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…For instance, an MRS study (Chen et al, 2014) found dynamic and transient metabolic alterations in the temporal lobe. Using TBSS, one DTI study demonstrated dynamic and complex WM microstructural changes in the earlier phases of RT (Duan et al, 2016). A multimodal study combining MRS and DTI (Xiong et al, 2013) reported significant alterations in both the metabolic and diffusion parameters of the WM that appeared normal in the temporal lobe.…”
Section: Introductionmentioning
confidence: 99%